Activated Factor X-Based versus Thrombin-Based Antithrombin Testing in Thrombophilia Workup in the DOAC Era - Rühl, Heiko; Reda, Sara; Müller, Jens; Oldenburg, Johannes; Pötzsch, Bernd (Thrombosis and Haemostasis, 2018)
Antithrombin (AT) activity tests are used for diagnosing hereditary AT deficiency, a main genetic determinant of thrombophilia. They are either based on inhibition of thrombin (FIIa) or activated factor X (FXa). FXa-based assays have been suggested to be preferable to FIIa-based assays due to their higher sensitivity for certain AT deficiency causing mutations. To assess the performance of these two methods in a real-world scenario, 745 consecutively collected samples from patients referred to our institute during a 3-month period for thrombophilia testing were analysed. In samples from patients not receiving direct-acting oral anticoagulants or heparins (n = 485), both methods showed good agreement (r = 0.874, Bland–Altman limits of agreement 6.57%, −15.76%). While similar results were obtained in patients receiving low-molecular-weight heparin (LMWH, n = 76, r = 0.891, 4.09%, −14.35%), the agreement was lower in patients receiving rivaroxaban (n = 86, r = 0.570, 5.97%, −49.43%) and apixaban (n = 72, r = 0.735, 3.77%, −42.45%). Direct FXa inhibitors but not LMWH increased FXa-based assay results in a dose-dependent manner, while the FIIa-based test was unaffected. Both assay types were equally successful in detecting hereditary AT deficiency in our study population, as samples from 9 out of 10 patients with AT deficiency causing mutations were detected by each method. These data suggest that FXa-based AT testing can be preferred over FIIa-based methods only in the absence of direct FXa inhibitors. In patients receiving direct FXa inhibitors, AT activity testing should be performed using FIIa-based assays.
Keywords: antithrombin deficiency; antithrombin assays; direct-acting oral anticoagulants; thrombophilia testing